2020
DOI: 10.3390/pr8091038
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Differentiation of Streptomyces clavuligerus Exposed to Diverse Environmental Conditions and Its Relationship with Clavulanic Acid Biosynthesis

Abstract: Clavulanic acid (CA) is a potent inhibitor of class A β-lactamase enzymes produced by Streptomyces clavuligerus (S. clavuligerus) as a defense mechanism. Due to its industrial interest, the process optimization is under continuous investigation. This work aimed at identifying the potential relationship that might exist between S. clavuligerus ATCC 27064 morphology and CA biosynthesis. For this, modified culture conditions such as source, size, and age of inoculum, culture media, and geometry of fermentation fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The author suggests that ORF21 plays a fundamental role in the transcription initiation of many genes commonly expressed in the exponential growth phase. In the current study, RNA samples were taken at the stationary growth phase (96 h), which is associated with morphological differentiation and nutritional stress [ 39 ]. During this time, ORF21 might not only affect the early steps of CA formation, as mentioned by Jnawali, but also the late steps.…”
Section: Discussionmentioning
confidence: 99%
“…The author suggests that ORF21 plays a fundamental role in the transcription initiation of many genes commonly expressed in the exponential growth phase. In the current study, RNA samples were taken at the stationary growth phase (96 h), which is associated with morphological differentiation and nutritional stress [ 39 ]. During this time, ORF21 might not only affect the early steps of CA formation, as mentioned by Jnawali, but also the late steps.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, for the first time, we tried to increase the apigenin biotechnological production by the recombinant S. albus-pAPI strain, also studying the pre-inoculum type. It is very well known that, due to the peculiar streptomycetes life cycle, the source, size, age and type of inoculum deeply influence the metabolism of the microorganism in the fermentation stage, and that it is a common practice to investigate inoculum conditions in process development studies to avoid unwanted and long lag phases, to reduce process time and to increase production yields [51]. For example, studies conducted on batch fermentations of Streptomyces clavuligerus demonstrated that both the inoculum age and type significantly impacted the production of clavulanic acid in industrial processes, particularly the productivity [52].…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies conducted on batch fermentations of Streptomyces clavuligerus demonstrated that both the inoculum age and type significantly impacted the production of clavulanic acid in industrial processes, particularly the productivity [52]. In many papers, authors preferred to use spores as inoculum, but in this case, a conditioning phase is required, that could last even several days, in order to induce germination [30,51]. In the streptomycetes life cycle, spores are more related to a quiescent phase which is used by the Streptomyces genus to survive to stressful environmental conditions, while the mycelial stage is actually more involved in the active synthesis of both primary and secondary metabolites [38,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Low temperatures favor the molecule stability; in this regard, higher titers have been reported during operating fermentations at 20 °C but the growth rate at such temperature is lower than that observed at 28 °C [ 70 , 71 ]. In addition, it has been found that both bacterial morphology in dispersed secondary mycelium and a high density spore suspension inoculum (with concentration ≥5%) significantly improve CA biosynthesis [ 72 , 73 , 74 ].…”
Section: Ca Production In S Clavuligerus Submementioning
confidence: 99%